Effects of porosity on the strength and mechanical behaviour of porous geo-materials under cyclic loading: Mechanics of Porous Geo-Materials (Rudarsko-geološko-naftni zbornik, 2024)
Most rocks in nature are porous and usually saturated with different fluids such as water, oil, and gas. The conventional and unconventional hydrocarbon reservoirs are mainly associated with sedimentary formations. The main rocks of these reservoirs are sandstone (porous rock), limestone and oil shale (tight rock), which are associated with varying porosity. Hence, porosity serves as a fundamental parameter for most reservoir rocks. In this research, the effect of porosity on the mechanical behaviour of geo-materials and its fatigue behaviour was investigated. For this purpose, a total of five geo-material sample groups with varying porosities were prepared and designated, i.e. groups A, B, C, D, and E. Group A exhibited the highest porosity 20-21.5%, while group E had the lowest porosity 2-3%, respectively. The conventional quasi-static strength tests and cycle loading tests with constant frequency and amplitude were performed on the samples and different results were obtained. The samples belonging to group E, with the lowest porosity (2-3%), exhibited the highest mechanical strength, elastic modulus and fracture toughness values and the lowest Poisson's ratio compared to those of higher porosity samples. During the cyclic loading period, the fatigue stress-life graph of the E group has the lowest slope compared to the other groups. It means that the slope of the graph increases as the porosity increases in all groups. Therefore, the E group has the lowest porosity and the longest fatigue life time, i.e. porosity and fatigue resistance have an inverse correlation.